2010
DOI: 10.1107/s1744309110035475
|View full text |Cite
|
Sign up to set email alerts
|

Unliganded structure of human bisphosphoglycerate mutase reveals side-chain movements induced by ligand binding

Abstract: PDB Reference: bisphosphoglycerate mutase, 3nfy.Erythrocyte-specific bisphosphoglycerate mutase is a trifunctional enzyme which modulates the levels of 2,3-bisphosphoglycerate (2,3-BPG) in red blood cells by virtue of its synthase and phosphatase activities. Low levels of erythrocyte 2,3-BPG increase the affinity of haemoglobin for oxygen, thus limiting the release of oxygen into tissues. 2,3-BPG levels in stored blood decline rapidly owing to the phosphatase activity of bisphosphoglycerate mutase, which is en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 45 publications
(45 reference statements)
3
4
0
Order By: Relevance
“…Structural studies of BPGM in complex with 2-PG in the absence and presence of 3-PGA (BPGMÁ3-PGAÁ2-PG and BPGMÁ2-PG complexes) showed not only bound 3-PGA and/ or 2-PG at the two active sites but also bound 2-PG at a novel binding site at the dimer interface; the first such report of the latter binding. As previously noted (Patterson et al, 2010) and observed in our crystallographic studies, Arg100, Arg116 and Arg117 and the C-terminal residues are very dynamic, which appears to be a structural determinant for catalysis. In monomer A of both the binary and ternary complexes, these residues are well ordered, resulting in a closed active-site conformation that is similar to that in previously published BPGM structures in complex with 2,3-BPG or 3-PGA (Wang et al, 2006).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Structural studies of BPGM in complex with 2-PG in the absence and presence of 3-PGA (BPGMÁ3-PGAÁ2-PG and BPGMÁ2-PG complexes) showed not only bound 3-PGA and/ or 2-PG at the two active sites but also bound 2-PG at a novel binding site at the dimer interface; the first such report of the latter binding. As previously noted (Patterson et al, 2010) and observed in our crystallographic studies, Arg100, Arg116 and Arg117 and the C-terminal residues are very dynamic, which appears to be a structural determinant for catalysis. In monomer A of both the binary and ternary complexes, these residues are well ordered, resulting in a closed active-site conformation that is similar to that in previously published BPGM structures in complex with 2,3-BPG or 3-PGA (Wang et al, 2006).…”
Section: Discussionsupporting
confidence: 84%
“…BPGM has two active sites in the C-terminal portion of an / domain of each monomer. The overall dimeric structure is identical to the previously published liganded and unliganded BPGM structures (PDB entries 1t8p, 2h4x, 2h4z, 2hhj and 3nfy; Wang et al, 2004Wang et al, , 2006Patterson et al, 2010).…”
Section: Crystallographic Study Of Bpgm In Complex With 3-pga and 2-pgsupporting
confidence: 74%
“…See also Figure S1. Patterson et al, 2010;Wang et al, 2004). However, L166 is invariant among vertebrates, and the L166P substitution is non-conservative, suggesting possible structural or functional effects on BPGM (Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
“…To examine protein stability, stably-transfected HEK293 cells expressing either wild-type BPGM L166 or the mutant BPGM P166 variant were treated with cycloheximide (100ug/mL; Sigma-Aldrich) for 2, 4, 6, 8, 12h, at which point cell lysates were prepared and analyzed by immunoblotting (anti-Flag antibody, 1:7000; Sigma-Aldrich, F1804-1MG). The L166 and P166 protein variants were modeled using the unliganded structure of human BPGM (PDB: 3NFY) using PyMOL (Patterson et al, 2010).…”
Section: Bpgm Protein Expression and Stabilitymentioning
confidence: 99%
“…Bisphosphoglycerate mutase (BPGM; EC: 5.4.2.4) is an erythrocyte-specific enzyme, and its main function is to regulate the oxygen affinity of hemoglobin by controlling the synthesis of 2.3-bisphosphoglycerate (DG2; C3 H8 O10 P2), which is an allosteric effector of hemoglobin, via a phosphoryl transfer reaction [ 15 , 20 ]. The deficiency of BPGM (BPGMD) increases the hemoglobin oxygen affinity, leading to a decrease in the DG2 concentration, and is characterized by hemolytic anemia [ 3 ].…”
Section: Methodsmentioning
confidence: 99%